Towards a trusted grid architecture - Cooper, A (2010)
The malicious host problem is challenging in distributed systems such as grids and clouds. Rival organisations may share the same physical infrastructure. Administrators might deliberately or accidentally compromise users' data. The thesis concerns the development of a security architecture that allows users to place a high degree of trust in remote systems to process their data securely. The problem is tackled through a new security layer that ensures users' data can only be accessed within a trusted execution environment. Access to encrypted programs and data is authorised by a key management service using trusted computing attestation. Strong data integrity and confidentiality protection on remote hosts is provided by the job security manager virtual machine. The trusted grid architecture supports the enforcement of digital rights management controls. Subgrids allow users to define a strong trusted boundary for delegated grid jobs. Recipient keys enforce a trusted return path for job results to help users create secure grid workflows. Mandatory access controls allow stakeholders to mandate the software that is available to grid users. A key goal of the new architecture is backwards compatibility with existing grid infrastructure and data. This is achieved using a novel virtualisation architecture where the security layer is pushed down to the remote host, so it does not need to be pre-installed by the service provider. A new attestation scheme, called origin attestation, supports the execution of unmodified, legacy grid jobs. These features will ease the transition to a trusted grid and help make it practical for deployment on a global scale.